Survival after whole brain radiotherapy for brain metastases from lung cancer and breast cancer is poor in 6325 Dutch patients treated between 2000 and 2014. (4th May 2018) - Jeene, Paul M.; de Vries, Kim C.; van Nes, Johanna G. H.; Kwakman, Johannes J. M.; Wester, Gerda; Rozema, Tom; Braam, Pètra M.; Zindler, Jaap D.; Koper, Peter; Nuyttens, Joost J.; Vos-Westerman, Hanneke A.; Schmeets, Ilona; et al.
Abstract: Background: Whole brain radiotherapy (WBRT) is considered standard of care for patients with multiple brain metastases or unfit for radical treatment modalities. Recent studies raised discussion about the expected survival after WBRT. Therefore, we analysed survival after WBRT for brain metastases 'in daily practice' in a large nationwide multicentre retrospective cohort. Methods: Between 2000 and 2014, 6325 patients had WBRT (20 Gy in 4 Gy fractions) for brain metastases from non-small cell lung cancer (NSCLC; 4363 patients) or breast cancer (BC; 1962 patients); patients were treated in 15 out of 21 Dutch radiotherapy centres. Survival was calculated by the Kaplan–Meier method from the first day of WBRT until death as recorded in local hospital data registration or the Dutch Municipal Personal Records Database. Findings: The median survival was 2.7 months for NSCLC and 3.7 months for BC patients ( p  < .001). For NSCLC patients aged <50, 50–60, 60–70 and >70 years, survival was 4.0, 3.0, 2.8 and 2.1 months, respectively ( p  < .001). For BC patients, survival was 4.5, 3.8, 3.2 and 2.9 months, respectively ( p  = .047). In multivariable analyses, higher age was related to poorer survival with hazard ratios (HR) for patients aged 50–60, 60–70 and >70 years being 1.05, 1.19 and 1.34, respectively. Primary BC (HR: 0.83) and female sex (HR: 0.85) were related to better survival ( p  < .001). Interpretation: The survival of patients after WBRT for brain metastases from NSCLC treated in Dutch 'common radiotherapy practice' is poor, in breast cancer and younger patients it is disappointingly little better. These results are in line with the results presented in the QUARTZ trial and we advocate a much more restrictive use of WBRT. In patients with a more favourable prognosis the optimal treatment strategy remains to be determined. Prospective randomized trials and individualized prognostic models are needed to identify these patients and to tailor treatment.